Excellent beauty: the naturalness of religion and the unnaturalness of the world - Dietrich, Eric (Columbia University Press, 2015)
Eric Dietrich is professor of philosophy at Binghamton University and the founding editor and current editor in chief of the Journal of Experimental and Theoretical Artificial Intelligence. He is the author of numerous papers and several books focusing on cognitive science, consciousness, artificial intelligence, metaphysics, epistemology, and philosophy of mind.